2021
DOI: 10.31373/ejtcm/134674
|View full text |Cite
|
Sign up to set email alerts
|

Attempt at profiling and regionalisation of COVID-19 vaccine campaigns in Poland - preliminary results

Abstract: This is Open Access article distributed under the terms of the Creative Commons Attribution-ShareAlike 4.0 International.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…As limited supplies are slowing vaccination campaigns in many countries, this is not the case in Poland, where delay in immunizing population reflects Poland-specific social background. It was already confirmed that social attitudes and context fundamentally impact the COVID-19 vaccine acceptance (Jarynowski and Skawina, 2021). Since the beginning of the COVID-19 pandemic, many studies have already been conducted to analyze why some Poles do not intend to vaccinate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As limited supplies are slowing vaccination campaigns in many countries, this is not the case in Poland, where delay in immunizing population reflects Poland-specific social background. It was already confirmed that social attitudes and context fundamentally impact the COVID-19 vaccine acceptance (Jarynowski and Skawina, 2021). Since the beginning of the COVID-19 pandemic, many studies have already been conducted to analyze why some Poles do not intend to vaccinate.…”
Section: Discussionmentioning
confidence: 97%
“…To assess social media influencers' engagement in the pro-vaccination campaign, the author conducted a systematic social media content analysis of Polish influencers' Instagram accounts from 27 December 2020, when the first person was vaccinated against COVID-19 in Poland (Jarynowski and Skawina, 2021), till 30 June 2021. Additionally, the author analyzed the content of direct messages from followers provided by some of the influencers.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, our knowledge of COVID-19 vaccines safety has been extended due to post registration passive surveillance (VAERS [North America] or ARR [European Union]) and active surveillance (as V-Safe (Shimabukuro, et al, 2021), Isrealian clinical trials (Barda, et al, 2021)). Immunisation against COVID-19 in Poland began on 27.12.2020 with Comirnaty vaccine with a priority given to healthcare workers and during the rst weeks only mRNA vaccines were available (Jarynowski & Skawina, 2021). Various Community based /participatory surveillance understood as "the detection and reporting of events of public health signi cance within a community by community members" (WHO, 2018) were created ad hoc and some people share their adverse events after immunisation in social media.…”
Section: Introductionmentioning
confidence: 99%
“…Social Media and social networks are a way to communicate with each other in such new circumstances. On the other hand, Polish society has a high proportion of negative attitudes towards vaccines (Jarynowski & Skawina, 2021). The widespread use of the Internet and social media provides us with an indispensable source of information on societal dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation